Sunlight Assisted Degradation of Methylene Blue as a Model Dye using Bismuth Oxychloride Nanoparticles: Ecofriendly and Industry Efficient Photocatalysis for Waste Chemical Treatment - Adhikari, Chandan; Kaur, Mandeep; Ravichandran (Asian Journal of Chemistry, 2019)
In this study, an efficient sunlight triggered dye degradation was demonstrated using methylene blue as a model dye and bismuth oxychloride nanoparticles were used as photocatalyst. Two different types of nanoparticles, nanoflower and nanodisk, were prepared to understand the effect of morphology on the photocatalysis. Both the particles were prepared following a straightforward and easy methodology from readily available chemicals. The particles were characterized using scanning electron microscope, Fourier transformed infrared spectroscopy, powder X-ray diffraction. UV-visible spectroscopy and colorimeter were used to evaluate the photocatalytic activity of the catalyst. Both the nanoparticles were able to degrade the dye completely within 3-4 h under visible light. The photocatalytic rate constant analysis demonstrates that out of two morphology, nanoflower is found to be more effective than nanodisk towards dye degradation. The sunlight was also used to understand whether the photocatalyst can degrade the dye or not in presence of sunlight only. Both nanoparticles were able to degrade the dye 100 % in presence of sunlight within maximum 4 h. The photocatalytic dye degradation in presence of sunlight was conducted in between 10 a.m. to 4 p.m. when the maximum amount of sunlight is available with high intensity and energy. The catalysts were 100 % active after the first cycle and upto four cycles the dye degradation efficiency remain around 60-80%. The study demonstrates that sunlight can degrade the dye in presence of these photocatalyst which clearly indicates its energy saving approach thus making it more economic and green methodology for the industries.